Circadian Phase Advances in Response to Weekend Morning Light in Adolescents With Short Sleep and Late Bedtimes on School Nights - Misiunaite, Ieva; Eastman, Charmane I.; Crowley, Stephanie J. (Frontiers in Neuroscience, 2020)
Many adolescents fall asleep too late to get enough sleep (8-10 h) on school nights. Morning bright light advances circadian rhythms and could help adolescents fall asleep earlier. Morning bright light treatment before school, however, is difficult to fit into their morning schedule; weekends are more feasible. We examined phase advances in response to morning light treatment delivered over one weekend. Thirty-seven adolescents (16 males; 14.7-18.0 years) who reported short school-night sleep (≤7 h) and late bedtimes (school-nights ≥ 23:00; weekend/non-school nights ≥ 24:00) slept as usual at home for ~2 weeks (“baseline”) and then kept a fixed sleep schedule (baseline school-night bed and wake-up times ± 30 mins) for ~1 week before living in the lab for one weekend. Sleep behavior was measures with wrist actigraphy and sleep diary. On Saturday morning, we woke each participant 1 h after his/her midpoint of baseline weekend/non-school night sleep and 1 h earlier on Sunday. They remained in dim room light (~20 lux) or received 1.5 h or 2.5 h of intermittent morning bright light (~6000 lux) on both mornings. The dim light melatonin onset (DLMO), a phase marker of the circadian timing system, was measured on Friday and Sunday evenings to compute the weekend circadian phase shift. The dim room light and 1.5-h bright light groups advanced the same amount (0.6±0.4 h and 0.6±0.5 h). The 2.5-h bright light group advanced 1.0±0.4 h, which was significantly more than the other groups. These data suggest that it is possible to phase advance the circadian clock of adolescents who have late bedtimes and short school-night sleep in one weekend using light that begins shortly after their sleep midpoint.